Bralne sposobnosti pri učencih različnih osnovnošolskih programov - Žgur, Erna (Socialno delo, 2017)
The paper compares the reading abilities of the 2nd grade primary school children and the 5th grade children in adapted education programme with a lower education standard. Three hypotheses were tested: time of reading aloud; number of mistakes during reading aloud; reading comprehension check by using questions. The results showed that the two groups are comparable only to the individual elements of the reading ability. The two groups have different mechanisms of functioning which is reflected in their reading abilities and their reading comprehension. Despite the differences, we determined that the effectiveness of the knowledge acquired in both groups is comparable, the differences having no statistical significance.
Keywords: branje; reading; special education; pouk po prilagojenem programu; prilagojeni programi; nižji izobrazbeni standard; intelektualni primanjkljaji; učna pomoč